THE CORRELATION BETWEEN READING HABIT AND TRANSLATING ABILITY FROM INDONESIA INTO ENGLISH - Hendriani Lesmana (IKIP Siliwangi, 2019)
Languange is important for all human beings in the world, we can communicate with each other from around the world..The main objective of this research entilted “The Correlation between Reading Habit and Translating Abiliy ” is to know whether there is correlation between reading habit and translating ability at the eleventh grade student senior high school This research used quantitative method. The sample in this research were 30 students of class eleventh grade senior high school. The instrument used questionnaire about reading habit and translating tests, then they are calculated by using Statistical Package for the Social Sciences (SPSS). With no significant level robs = 0.119, the result of the test shows that there is negative correlation between reading habit and translating ability with correlation value r is 0.533. It can be concluded that there is a no significant relationship between reading habit and translating ability of the eleventh grade students of senior high school with low level correlation. This means that reading habits no effect for translating ability.Keyword : Correlation, Reading Habit, Translating Ability